Enrooting algorithms: a scoping review on the proliferation of artificial intelligence and ensuing implications of the rising human-machine symbiosis for firms - Gonçalves, Renato Miguel Sopa Martinho (2022)
The diffusion of Artificial Intelligence and Machine Learning could herald the dawn of the fourth industrial revolution; yet, irrespective of their value-laden potential, thorough establishment of such processes in firms is onerous. Given the significance of the technologies for the sustainability of companies in increasingly competitive markets, a scoping review was conducted to aggregate the findings of emerging literature regarding the growing prominence of algorithms. The results highlight the predominance of augmentation practices and that, despite the ensuing restructuring and hindrances’ complexity, the promise of the technologies merits involvement in the intricate measures that mitigate risks and culminate in upscaling.